PENERAPAN MODEL TEAM ASISSTED INDVIDUALIZATION (TAI) DALAM PENINGKATAN PEMBELAJARAN IPS SISWA KELAS IV SD - Tanjung, Zahro Sri (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: Application of Team Asissted Individualization (TAI) models in Social Studies Learning 4th Grade Fractional Elementry School . The purpose of this research to increase social studies fourth grade students in the elementary school by application of models TAI. This research is a collaborative classroom action research. This study was conducted in two cycles. Each cycle consists of planning, observation, implementation, and reflection. The data comes from the fourth grade students, observer, and fourth grade teacher. Submit techniques with test, observations, questionnaires, and documentation. The validity of the data using descriptive analysis techniques qualitative and quantitative. The conclusion of this research is the application of models TAI can improve learning social studies fourth grade students elementary school. Keywords: Team Asissted Individualization (TAI), Social Studies Learning Abstrak: Penerapan Model Team Asissted Indvidualization (TAI) dalam Peningkatan Pembelajaran IPS Siswa Kelas IV SD. Tujuan penelitian ini adalah untuk meningkatkan pembelajaran IPS siswa kelas IV di SD dengan penerapan model TAI. Penelitian ini merupakan penelitian tindakan kelas kolaboratif yang dilaksanakan dalam 2 siklus. Setiap siklus terdiri dari tahap perencanaan, pelaksanaan, observasi, dan refleksi. Subjek penelitian ini adalah siswa kelas IV dan guru kelas IV SD. Data berasal dari siswa kelas IV, observer, dan guru kelas IV. Teknik pengumpulan data dengan tes, observasi, kuesioner, dan dokumentasi. Validitas data menggunakan teknik analisis deskriptif kualitatif dan kuantitatif. Simpulan penelitian ini adalah penerapan model TAI dapat meningkatkan pembelajaran IPS siswa kelas IV SD. Kata Kunci: Team Asissted Individualization (TAI), Pembelajaran IPS